Review of the European Society of Cardiology Guidelines for the management of infective endocarditis in patients with cardiac implantable electronic devices - M.Т. Vatutin; A.M. Shevelok; Ye.V. Kartamysheva; A.O. Taratorina; K.S. Gasendich; Ye.V. Yeshchenko; Yu.P. Gritsenko; О.К. Stavynska (Кардіохірургія та інтервенційна кардіологія)
Review of the current guidelines for management of patients with infective endocarditis is provided in this article. The information about diagnosis, medical and surgical treatment of infective endocarditis in patients with cardiac implantable electronic devices and prosthetic valve endocarditis, prophylaxis and anticoagulanttherapy is provided.